2010
DOI: 10.1103/physrevb.81.125405
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures: Scattering beyond the Born approximation

Abstract: The neutron scattering on a two-dimensional ordered nanostructure with the third nonperiodic dimension can go beyond the Born approximation. In our model supported by the exact theoretical solution a well-correlated hexagonal porous structure of anodic aluminum oxide films acts as a peculiar two-dimensional grating for the coherent neutron wave. The thickness of the film L ͑length of pores͒ plays important role in the transition from the weak to the strong scattering regimes. It is shown that the coherency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…In the IMS, the intensity depends further on the reduced area of SS regions, while the peaks broaden due to the finite size of VL domains. Note, that the observed correlation length is much larger for small angle diffraction [42], compared to diffuse SANS [43].…”
Section: Acknowledgmentsmentioning
confidence: 91%
See 1 more Smart Citation
“…In the IMS, the intensity depends further on the reduced area of SS regions, while the peaks broaden due to the finite size of VL domains. Note, that the observed correlation length is much larger for small angle diffraction [42], compared to diffuse SANS [43].…”
Section: Acknowledgmentsmentioning
confidence: 91%
“…The VL-correlation length ξ V L obtained from SANS measurements was determined from the width of the first order Bragg-peaks ∆q Bragg in q-direction. It was corrected by the reciprocal space resolution ∆q Inst according to [34,42] as ∆q = ∆q 2 Bragg − ∆q 2 Inst . The VLcorrelation length is then defined as ξ V L = (2π)/(∆q) The Bragg peak positions are defined by the VL arrangement (structure factor).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In some cases, especially in low-symmetry crystals, t z = t z (k x , k y ) depends on in-plane momentum, which affects AMRO and MQO. [22][23][24][25] However, to describe most compounds it is sufficient to take t z (k x , k y ) ≈ const. The geometrical explanation of AMRO 5 for the electron dispersion in Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, small angle neutron scattering from an AAO matrix was theoretically described in [32]. It was shown that description of the scattering process is beyond the scope of the Born approximation.…”
Section: Introductionmentioning
confidence: 99%